Pengaruh Jumlah Kredit, Simpanan, Nasabah, Dan Tenaga Kerja Terhadap Pendapatan LPD Di Kecamatan Denpasar Selatan Tahun 2005-2011 - Ratna, Mirah Desy; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 2, Februari 2013 (pp. 63-118), 2013)
The government's efforts to reduce inequality and poverty through various programs, such as: Presidential Instruction (Instruction), and the provision of credit to the economically weak communities in rural areas to increase employment opportunities, productivity and business opportunities. The research was conducted on LPD in South Denpasar District which aims to determine the effect of the amount of credit, deposits, number of customers, and the amount of labor to revenue LPD in South Denpasar District. Data analysis techniques used in this research is the analysis of multiple linear regression with an error rate of 5 percent (0.05). Before performing the multiple linear regression analysis. The results of this study indicate that variable amounts of credit, deposits, number of customers, and the number of workers affected by partial to income LPD in South Denpasar District with a significance value of less than 5%. Simultaneous testing showed that the number of loans, deposits, number of customers, and a significant amount of labor to revenue LPD in South Denpasar District.
Keywords: credit; deposits; number of customers; amount of labor to revenue